Optical, electrical and microstructural properties of nanocomposite Ag/diamond by Ag ion implantation and subsequent annealing. (January 2016) - Shen, Yanyan; Qi, Ting; Qiao, Yu; Hei, Hongjun; He, Zhiyong; Yu, Shengwang
Abstract: An optical-grade, free-standing diamond (FSD) film is prepared by home-made microwave plasma chemical vapor deposition reactor at a condition of input power 8 kW and gas pressure18 kPa. Then, it is implanted with 80 keV Ag ions up to a fluence of 5.0 × 1016 ions/cm 2 . After implantation, a subsequent annealing in Ar ambient at 500 °C is carried out to fabricate Ag nanoparticles (NPs). Grazing incidence x-ray diffraction results clearly showed that Ag NPs with a (111) orientation are effectively formed after 500 °C annealing. Results from field emission scanning electron microscope and atomic force microscope observations indicated that Ag NPs could aggregate and grow on the surface of the diamond film during the annealing process. The Hall effects results showed that Ag-implanted FSD film exhibited an enhanced carrier mobility of 34.7 cm 2 V −1 S −1 after 500 °C annealing. Moreover, Raman spectroscopy results show that the damages of the Ag-implanted FSD film are essentially a little and the crystallinity is almost recovered by annealing, it is implied that the enhancement in carrier mobility could be attributed to the conductive paths provided by Ag NPs. Highlights: Ag nanoparticles were fabricated in the free-standing diamond film by ion implantation. Ag SPR peak at about 375 nm appears after 500 °C annealing. Ag-embedded FSD films exhibited an enhanced carrier mobility after 500 °C annealing. Ag nanoparticles act as conductive paths permitting charges to pass through them. The Ag-embedded free-standing diamond films still shows high sp 3 -bonds.